Long-term accumulation of macro- and secondary elements in subtropical treatment wetlands - Reddy, K.R.; Hu, J.; Villapando, O.; Bhomia, R.K.; Vardanyan, L.; Osborne, T. (Wiley, 2021)
The Everglades Stormwater Treatment Areas (STAs) are a complex of large constructed wetlands that are an integral component of the State and Federal efforts to restore the Everglades ecosystem. The overall objective of this study was to determine the accumulation rates of macro-elements including carbon (C), nitrogen (N), phosphorus (P), sulfur (S), and associated secondary elements including calcium (Ca), magnesium (Mg), aluminum (Al), and iron (Fe) in two Everglades STAs over their periods of operation. The study was conducted in STA-2 with parallel flow-ways consisting of emergent aquatic vegetation (EAV) and submerged aquatic vegetation (SAV) and the Western flow-way of STA-3/4 with EAV and SAV cells operated in series. Elemental accumulation rates were determined in the unconsolidated surficial sediments (floc) and recently accreted soil (RAS) that have accumulated on top of the antecedent soil over the 14- and 10-yr periods of operation for STA-2 and STA-3/4, respectively. Flow-ways with SAV were more efficient than EAV in accreting mineral matter, resulting in increased bulk density and higher accumulation rates of elements. Average C accumulation in the floc and RAS of SAV flow-ways was 320 g·m−2·yr−1 with approximately equal proportions of inorganic and organic C, while in the EAV flow-ways accumulation rates of C ranged from 116 to 147 g·m−2·yr−1 with mostly organic C. Phosphorus accumulation rates were approximately 2–3 times higher in SAV than in EAV flow-ways. Differences in accumulation of elements between SAV and EAV were largest for Ca with 17–42 times more Ca in SAV than EAV systems. This suggests that in the SAV systems, possible occlusion of macro-elements and metals during CaCO3 precipitation facilitated accretion of material with high mineral content. In EAV, biomass turnover and associated biotic processes regulated organic matter accumulation rates. The spatial accumulation patterns of P, C, and N in the EAV areas of STA-2 and STA-3/4 were similar to those observed in the EAV areas of the natural wetlands in Water Conservation Areas, suggesting that constructed wetland systems function similarly to natural wetlands dominated by EAV areas in retaining and storing macro- and secondary elements.